Risk factors for anti‐drug antibody formation to infliximab: Secondary analyses of a randomised controlled trial. (26th April 2022) - Brun, Marthe Kirkesæther; Goll, Guro Løvik; Jørgensen, Kristin Kaasen; Sexton, Joseph; Gehin, Johanna Elin; Sandanger, Øystein; Olsen, Inge Christoffer; Klaasen, Rolf Anton; Warren, David John; Mørk, Cato; Kvien, Tore K.; Jahnsen, Jørgen; et al.
Abstract: Background: Anti‐drug antibodies (ADAb) frequently form early in the treatment course of infliximab and other tumour necrosis factor (TNF) inhibitors, leading to treatment failure and adverse events. Objective: To identify risk factors for ADAb in the early phase of infliximab treatment. Methods: Patients ( n = 410) with immune‐mediated inflammatory diseases who initiated infliximab treatment were included in the 38‐week Norwegian Drug Monitoring Trial (NOR‐DRUM) A and randomised 1:1 to therapeutic drug monitoring (TDM) or standard therapy. Serum levels of infliximab and ADAb were measured at each infusion. Possible risk factors for ADAb formation were assessed using logistic regression, adjusting for potential confounders. Results: ADAb were detected in 78 (19%) patients. A diagnosis of rheumatoid arthritis (RA) (odds ratio [OR], 1.9 [95% confidence interval [CI] 1.0–3.6]) and lifetime smoking (OR, 2.0 [CI 1.1–3.6]) were baseline risk factors, while baseline use of concomitant immunosuppressors (OR, 0.4 [CI 0.2–0.8]) and a diagnosis of spondyloarthritis (SpA) (OR, 0.4 [CI 0.2–0.8]) reduced the risk of ADAb. Higher disease activity during follow‐up (OR, 1.1 [CI 1.0–1.1]) and "drug holidays" of more than 11 weeks (OR, 4.1 [CI 1.2–13.8]) increased the risk of ADAb, whereas higher infliximab doses (OR, 0.1 [CI 0.0–0.3) and higher serum infliximab concentrations (OR, 0.7 [CI 0.6–0.8]) reduced the risk of immunogenicity. Conclusion: Several risk factors for ADAb formation during early‐phase infliximab treatment were identified. This knowledge provides a basis for treatment strategies to mitigate the formation of ADAb and identify patients in whom these measures are of particular importance. Abstract :